Distinct Ultradian Rhythms in Plasma Clusterin Concentrations in Lean and Obese Korean Subjects - Jong Han Choi; Eunheui Jeong; Byung Soo Youn; Min-Seon Kim (Endocrinology and Metabolism, 2018)
BackgroundBlood levels of many hormones show rhythmic fluctuations with variable duration of cycles. Clusterin/apolipoprotein J is a glycoprotein which is highly expressed in the plasma and has modulatory roles in immune and inflammatory reactions, neurobiology, lipid metabolism, and leptin signaling. In this study, we examined the diurnal fluctuations of plasma clusterin concentrations in lean and obese young men.MethodsFor the study, 14 subjects (five lean and five obese men; two lean and two obese women) were admitted to the research ward and blood samples were drawn every 30 minutes during light-on period (6:00 AM to 10:00 PM) and every hour during light-off period.ResultsNotably, plasma clusterin concentrations displayed a unique ultradian rhythm with five cycles a day in both men and women. During the light-on period, circulating clusterin levels showed fluctuating curves with 4 hours regular intervals with sharp peaks and troughs. In contrast, single oscillation curve during light-off exhibited a smoothened/lower peak and longer (8-hour) duration. In obese men, these cycles were phase-advanced by approximately 1 hour, and had reduced amplitude of fluctuating curves and blunted diurnal pattern. Cyclic fluctuations of plasma clusterin were preserved under fasting and unexpected meal condition, suggesting that rhythmic oscillations in plasma clusterin levels are not generated by meal-related cues.ConclusionThese findings firstly demonstrate a novel pattern of plasma clusterin fluctuations with extremely regular cycles.